Reflections on systemization and development of Islamic moral studies - Malik, Mohammad Manzoor (2011)
The paper addressed reflections on systemization and development of Islamic moral studies with the premise that Islamic moral studies should be based on Islamic ethics as a discipline. The paper demonstrated that the subject matter of Islamic ethics is inclusive of habits, character, and behavior. Therefore, Islamic ethics ought to be redefined and developed in the fashion to address adequately metaethical, normative, and applicative aspects of the subject. On metaethical level, Islamic ethics should be connected with Islamic worldview, based on the original sources of Islamic knowledge, and on normative and applicative levels, it should be based on principles of Islamic jurisprudence (Uṣūl al-fiqh). The paper, further demonstrated that Islamic ethics contains both psychological and behavioral aspects; therefore, it transcends the division between virtue ethics and personality ethics, therefore, a synthetic model is closer to essence of Islamic teachings. The researcher, finally, argued that Islamic virtues should be made operational and executable in a way to be more relevant to the practical realm for the better social transformation. In attaining these objectives, both children and adults need to be given practical, analytical, and normative training in making moral choices. At school level, this could be done by involving problem solving methods, case studies, dilemmas, and anecdotes.